Exceptionally Warm and Prolonged Flow of Warm Deep Water Toward the Filchner-Ronne Ice Shelf in 2017 - Ryan, Svenja; Hellmer, Hartmut H; Janout, Markus; Darelius, Elin; Vignes, Lucie; Schröder, Michael (Geophysical Research Letters, 2020)
The Filchner-Ronne Ice Shelf, fringing the southern Weddell Sea, is Antarctica's second largest ice shelf. At present, basal melt rates are low due to active dense water formation; however, model projections suggest a drastic increase in the future due to enhanced inflow of open-ocean warm water. Mooring observations from 2014 to 2016 along the eastern flank of the Filchner Trough (76°S) revealed a distinct seasonal cycle with inflow if Warm Deep Water during summer and autumn. Here we present extended time series showing an exceptionally warm and long inflow in 2017, with maximum temperatures exceeding 0.5°C. Warm temperatures persisted throughout winter, associated with a fresh anomaly, which lead to a change in stratification over the shelf, favoring an earlier inflow in the following summer. We suggest that the fresh anomaly developed upstream after anomalous summer sea ice melting and contributed to a shoaling of the shelf break thermocline.
Keywords: Sørishavet; Weddellhavet; batymetri; brehylle; geofysikk; havis; isbrem; kontinentalsokkel; oseanografi; sjøis; smelting

The Weddell Gyre, Southern Ocean: Present Knowledge and Future Challenges - Vernet, M; Geibert, Walter; Hoppema, Mario; Brown, Peter J; Haas, Christian; Hellmer, Hartmut H; Jokat, Wilfried; Jullion, L; Mazloff, M; Bakker, D C E; Brearley, J A; Croot, Peter L; et al. (Reviews of Geophysics, 2019)
The Weddell Gyre (WG) is one of the main oceanographic features of the Southern Ocean south of the Antarctic Circumpolar Current which plays an influential role in global ocean circulation as well as gas exchange with the atmosphere. We review the state-of-the art knowledge concerning the WG from an interdisciplinary perspective, uncovering critical aspects needed to understand this system's role in shaping the future evolution of oceanic heat and carbon uptake over the next decades. The main limitations in our knowledge are related to the conditions in this extreme and remote environment, where the polar night, very low air temperatures, and presence of sea ice year-round hamper field and remotely sensed measurements. We highlight the importance of winter and under-ice conditions in the southern WG, the role that new technology will play to overcome present-day sampling limitations, the importance of the WG connectivity to the low-latitude oceans and atmosphere, and the expected intensification of the WG circulation as the westerly winds intensify. Greater international cooperation is needed to define key sampling locations that can be visited by any research vessel in the region. Existing transects sampled since the 1980s along the Prime Meridian and along an East-West section at ~62°S should be maintained with regularity to provide answers to the relevant questions. This approach will provide long-term data to determine trends and will improve representation of processes for regional, Antarctic-wide, and global modeling efforts—thereby enhancing predictions of the WG in global ocean circulation and climate.
Keywords: Sørishavet; Weddellhavet; biologi; brehylle; geologi; havis; havstrømmer; isbrem; isshelf; kjemi; oseanografi; sjøis; vannmasser; vannvirvler